IMPLEMENTASI LOGIKA FUZZY DENGAN MENGGUNAKAN METODE MAMDANI UNTUK MENENTUKAN PENERIMAAN BEASISWA DARI YAYASAN RUMAH ZAKAT - luthan, nanda (Jurnal EDik Informatika, 2017)
the scholarship is an educational assistance provided by an institution or non agency, agencies that are given to students who are top achievers or less capable in order to support the students ' learning process. Rumah zakat is one of the agencies that provide assistance or scholarship for school students in Batam city, for this process, there is no special way or mathematical calculations used this process for Rumah zakat, thus allowing the scholarship is not right on targetMamdani fuzzy logic is fuzzy logic by using a function, Mamdani method can be implemented in the decision-making, as do determine the selection of scholarship recipients, by implementing fuzzy logic for the selection process for the scholarship recipients, then the results obtained will be more precisely targeted, because the process is generated based on calculation mathematically.